PECULIARITIES OF THERAPY WITH LONG ACTING β2-ADRENERGIC AGONISTFORMOTEROL FOR ASTHMA IN CHILDREN - Yu.G. Levina; L.S. Namazova; V.V. Botvin'eva; N.I. Voznesenskaya; R.M. Torshkhoeva; K.E. Efendieva (Union of pediatricians of Russia, 2006)
Information on clinical use of long acting β2-adrenergic agonist formoterol in children with asthma is presented. Pharmacokinetics and pharmacodymanics are scrutinized in detail. Combined therapy for asthma with formoterol and inhaled corticosteroids is spotlighted.Key words: formoterol, asthma, children.